2014
DOI: 10.1002/2013jc009156
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton community structure and dynamics in the Arctic Canada Basin during a period of intense environmental change (2004-2009)

Abstract: Mesozooplankton were sampled in the Canada Basin in the summers of 2004, 2006, 2007, 2008, and fall 2009. Six taxa (Calanus hyperboreus, Calanus glacialis, Oithona similis, Limacina helicina, Microcalanus pygmaeus, and Pseudocalanus spp.) accounted for 77–91% of the abundance in all years, and 70–80% of biomass in 2004–2008. The biomass of C. hyperboreus and C. glacialis was reduced in 2009, likely due to seasonal migration below the sampling depth. Mean abundance was consistent across surveys while biomass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…David et al (2015) observed that the under-ice metazoan community structure differed between a densely ice-covered 'Nansen Basin regime' (corresponding to the Atlantic regime in the present study), and a more open 'Amundsen Basin regime' (the Shelf-influenced regime in the present study) in summer 2012. Our observation that sea-ice concentration was an important factor structuring the epipelagic metazoan community (Table 3) is in agreement with a multi-annual study in the Western Arctic Ocean finding that the contribution of sea-ice concentration to the variability in zooplankton community structure ranked highest together with bathymetry among numerous investigated environmental parameters (Hunt et al 2014). In the epipelagic metazoan community ordination, crossing gradients of sea-ice properties (SIC) and shelf influence (S.ML, Si) indicated that, in combination with sea-ice influence, the epipelagic metazoan community structure responded to shelf influence (Fig.…”
Section: Taxonomic Community Structuresupporting
confidence: 91%
“…David et al (2015) observed that the under-ice metazoan community structure differed between a densely ice-covered 'Nansen Basin regime' (corresponding to the Atlantic regime in the present study), and a more open 'Amundsen Basin regime' (the Shelf-influenced regime in the present study) in summer 2012. Our observation that sea-ice concentration was an important factor structuring the epipelagic metazoan community (Table 3) is in agreement with a multi-annual study in the Western Arctic Ocean finding that the contribution of sea-ice concentration to the variability in zooplankton community structure ranked highest together with bathymetry among numerous investigated environmental parameters (Hunt et al 2014). In the epipelagic metazoan community ordination, crossing gradients of sea-ice properties (SIC) and shelf influence (S.ML, Si) indicated that, in combination with sea-ice influence, the epipelagic metazoan community structure responded to shelf influence (Fig.…”
Section: Taxonomic Community Structuresupporting
confidence: 91%
“…Spatial variability in particle flux may reflect seasonal variations in ice cover and associated primary productivity, lateral supply of resuspended sediments, and the distance from land and the shelf break. Primary production in summer is highest in the southwestern part of the Canada Basin [ Nishino et al ., ; Varela et al ., ; Hunt et al ., ], and hence the spatial distribution of the observed particle flux is consistent with that of primary production. However, the summer POC flux comprised only a minor portion of the annual POC flux.…”
Section: Discussionmentioning
confidence: 99%
“…For example, underestimated grazing might allow high Chl-a even with low nutrient values, or the model system might be especially tuned to thrive under low-nutrient conditions. A simplified ecosystem model, e.g., representing only single phytoplankton, zooplankton, and N based nutrient species, does not allow the model to shift from larger to smaller phytoplankton species over time as suggested by Li et al [2009], to represent different depth occupations by different species [Monier et al, 2014], allow preferences for zooplankton species with multiple life stages [Hunt et al, 2014]. Hence, the use of a simple NPZD model might cause the model to represent a very defined SCM, with not much other production or, if tuned differently only represent a surface community.…”
Section: Ecosystem Complexitymentioning
confidence: 99%